Budaya modern mengalami perkemba Reinterpretasi Adab Jawa Dalam Karya Seni Lukis: Perspektif Generasi Z dan Alpha: Adab Jawa Dalam Karya Seni Lukis: Perspektif Generasi Z dan Alpha - Hafidh Nur Alfarizi; Amir Gozali (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This article highlights significant changes in Javanese society, particularly among Generation Z and Alpha, who are increasingly distancing themselves from traditional cultural values due to the influence of modern culture. In this context, the author created a painting titled